Effect of the use of music on definitional knowledge in an introductory statistics course: Evidence from a Pareto chart activity. (16th April 2021) - Anderson, Jan L.; Krasnozhon, Leonid A.
ABSTRACT: The traditional instructional approach combined with standard textbook examples provide a disengaging learning environment for students in introductory statistics courses. This article proposes and examines an experiential music‐based single‐class‐period learning activity for an introductory statistics course. This activity teaches students how to use graphical presentation of descriptive statistics, such as bar, pie, and Pareto charts. Studies in psychology and consumer research demonstrate that the music has positive short‐term effects on spatial‐temporal reasoning and sensorial response. We use a preclass postclass control‐group design to examine how the change of the method of instruction affects learning outcome. We find that the music‐based experiential learning activity has a positive effect on the definitional knowledge acquired by male students and students with higher grade point averages.